FIVE BASIC ACCOUNTING CONCEPTS. - Pilcher, D. J. (The Accounting Review, 1933)
Effectiveness in teaching, because of the vast amount of material offered in the average course in accounting, may be determined by the approach selected and the material emphasized during a period of instruction. The importance of this statement is the reason that efforts are constantly made to learn of new methods which may in some degree increase the student's general comprehension of the science, as of March 1933. In this article a skeleton-plan consisting of five accounting concepts and detailed explanation of three aspects of the accounting mechanism is presented. The proposed plan is made up of three parts. The first part consists in sketching in the early lectures a general view of the field by aid of five basic concepts which, with adequate refinements, begins with the account and ends with the financial and income statements. The second part consists of intense study of the account, the accounting equation, the accounting records, the accounting period and the work sheet. The third part, which reviews in a general fashion the foregoing, consists of thorough analysis and explanation of the accounting equation, inventories and the adjusting entries section of the work sheet.